1988
DOI: 10.1016/0035-9203(88)90446-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxocara canis infection in tropical Venezuela

Abstract: An enzyme-linked immunosorbent assay (ELISA) was used to determine the seroprevalence of Toxocara canis infection in different socio-economic groups of the tropical population of Venezuela. The lack of definitive independent diagnostic criteria for toxocariasis required the establishment of operational upper limits of normality for Toxocara ELISA values, based upon their log-normalized distribution in a presumptive "non-toxocariasis" sub-population. Only 1.8% of urban subjects of medium-high socio-economic lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 28 publications
5
25
0
Order By: Relevance
“…This value is among the values of frequency previously found in other places from our country [7][8][9]30,31 and relatively similar with other studies from other Latin American countries 2,3,21,27 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This value is among the values of frequency previously found in other places from our country [7][8][9]30,31 and relatively similar with other studies from other Latin American countries 2,3,21,27 .…”
Section: Discussionsupporting
confidence: 93%
“…*Some subjects had more than one sign/symptom; **p < 0.05 = significant value (Chi-square); *** variables in the model: sex, age, pulmonary and hepatic manifestations, headache, and weakness and/or fatigue. In agreement with other authors, we have also found statistically significant differences between gender and positive serology indicating that male subjects are more associated at risk of toxocariasis than female subjects, probably because of their close contact with soil, as is the case with this population, who are farmers 4,5,21,22,26 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Different rates have been reported ranging from 1% in Spain 28 to 86% in Santa Lucia 35 ; 3.6% to 24.7% in Brazil 2,9 ; 47.5% in Colombia 1 ; 34.9% to 66.6% in Venezuela 14,22 , and 37.9% to 39% in Argentina 3,30 . In Peru, limited reports indicate frequencies of 7.8% to 20% in rural population and 40% in subjects with ocular suspicion 12,13,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The first studies in the country found up to 66.6 % seroprevalence in children 2 -7 years old of Caracas [59]. In Ameridians from the Venezuelan Amazon region, a seroprevalence of 34.9 % was reported in 1988 [60]. Most studies in the country have been limited to short case series or even case reports.…”
Section: Toxocariasis In Venezuelamentioning
confidence: 99%